Altered cerebellar connectivity in Parkinson's patients ON and OFF L-DOPA medication - Festini, Sara B.; Bernard, Jessica A.; Kwak, Youngbin; Peltier, Scott; Bohnen, Nicolaas I.; Müller, Martijn L. T. M.; Dayalu, Praveen; Seidler, Rachael D. (Frontiers in Human Neuroscience, 2015)
Although nigrostriatal changes are most commonly affiliated with Parkinson’s disease, the role of the cerebellum in Parkinson’s has become increasingly apparent. The present study used lobule-based cerebellar resting state functional connectivity to (1) compare cerebellar-whole brain and cerebellar-cerebellar connectivity in Parkinson’s patients both ON and OFF L-DOPA medication and controls, and to (2) relate variations in cerebellar connectivity to behavioral performance. Results indicated that, when contrasted to the control group, Parkinson’s patients OFF medication had increased levels of cerebellar-whole brain and cerebellar-cerebellar connectivity, whereas Parkinson’s patients ON medication had decreased levels of cerebellar-whole brain and cerebellar-cerebellar connectivity. Moreover, analyses relating levels of cerebellar connectivity to behavioral measures demonstrated that, within each group, increased levels of connectivity were most often associated with improved cognitive and motor performance, but there were several instances where increased connectivity was related to poorer performance. Overall, the present study found medication-variant cerebellar connectivity in Parkinson’s patients, further demonstrating cerebellar changes associated with Parkinson’s disease and the moderating effects of medication.